SYNTHESIS OF BLACK TURMERIC EXTRACT NANOPARTICLES (CURCUMA CAESIA) AND ITS CYTOTOXIC ACTIVITY ON T47D CELLS - DA’I, MUHAMMAD; AZIZAH, NUR; RAHMANA, ANDREA Y; NURWAINI, SETYO; WIKANTYASNING, ERINDYAH R (International Journal of Applied Pharmaceutics, 2024)
Objective: This study aimed to formulate black turmeric into nanoparticle preparations with various concentrations of chitosan and determine its cytotoxic effect on T47D breast cancer cells. Methods: Extraction was carried out by the maceration method. Black turmeric condensed extract was formulated into nanoparticles using the ionic gelation method, which was a method that relies on the cross-linking agent sodium tripolyphosphate (Na-TPP). The cytotoxic activity of black turmeric extract was tested using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay method. Results: The results showed that black turmeric extract nanoparticles have a size range of 266-558 nm and were positively charged with zeta potential values ​​ranging from 3.3 to 9.7 mV. The encapsulation efficiency of black turmeric extract nanoparticles was 63.42%. The results of the cytotoxic test showed that both black turmeric extract and black turmeric extract nanoparticles showed moderate cytotoxic activity, with the IC50 values ​​of the two preparations were 78.60 µg/ml and 162.95 µg/ml, respectively. Conclusion: The results obtained in this research indicate a promising potential of nanoparticles of black turmeric extract as a cytotoxic agent for the treatment of breast cancer.